1)=8а²(в²-9с²)=8а²(в-3с)(в+3с).
2)=2(х²-12ху+36у²)=2(х-6у)².
3)=-2а(4а4-4а²+1)= -2а(2а²-1)².
4)=5(а³-8в6)=5(а³-(2в²)³)=5(а-2в²)(а²+2ав²+4в4)
5)=(а³+а²)-(ав-а²в)=а²(а+1)-ав(1+а)=(а+1)(а²-ав)=а(а+1)(а-в)
6)=с4(а-1)-с²(а-1)=(а-1)(с4-с²)=с²(а-1)(с²-1)=с²(а-1)(с-1)(с+1).
1)=(х-у)²-7²=(х-у-7)(х-у+7)
2)=а²-(3в-с)²=(а+3в-с)(а-3в+с)
3)=(в³)²-(2в²-3)²=(в³+2в²-3)(в³-2в²+3).
4)=(m³+3³n³)+(m+3n)²=(m+3n)(m²-3mn+9n²)+(m+3n)²=(m+3n)(m²-3mn+9n²+m+3n).
5)=x²-y²+2x+4y-3=(x²+2x+1)-(y²-4y+4)=(x+1)²-(y-2)²=(x+y-1)(x-y+3).
y+|x|-3=0
x>=0 y=3-x
x<0 y=3+x
y-|x-1|=0
x>=1 y=x-1
x<1 y=1-x
2-|x|+2y=0
x>=0 y=x/2-1
x<0 y=-1-x/2
3y-|2x-6|=0
2x-6>=0 x>=3 3y-2x+6=0 3y=2x-6 y=2x/3-2
x<3 3y+2x-6=0 3y=6-2x y=-2x/3+2